(untitled) (Bangladesh Journal of Medical Microbiology, 2025)
Background: Acute respiratory infections caused by a multitude of microorganisms, including viruses and bacteria are wide spread and are characterized by overlapping clinical presentations. Objective: This study utilized a multiplex real-time PCR Respiratory Panel for early, accurate and simultaneous detection of multiple respiratory pathogens in a single test that plays a crucial role in guiding antibacterial and/or antiviral therapy. Methodology: This retrospective study was conducted in molecular laboratory of Square Hospitals Ltd. Nasopharyngeal and/or oropharyngeal swabs were collected from patients of all age groups with suspected acute respiratory infections from each setting like IPD, OPD and critical care of the hospital from March 2023 to October 2023. Both viral and bacterial detection were performed following DNA/RNA extraction and Multiplex real-time PCR using VIASURE Respiratory Panel III kit for the period of 8 months. Results were analyzed by software according to manufacturer instructions. Results: Among 569 respiratory samples tested, 442(77.7%) samples were positive and total 784 pathogens were detected including virus (42.1%) and bacteria (57.9%), represented as single or co-infection. Of total positives, 70.2% cases were from adults and 29.8% cases from children. Isolation of bacteria was more than virus in both age group with highest prevalence of Streptococcus pneumoniae (53%; 38%) followed by Haemophilus influenzae and Moraxella catarrhalis. The most common detection was Influenza A virus (30%) followed by Respiratory Syncytial Virus (17%), Rhino Virus (15.0%) and Influenza B virus (13%). The overall positive rate for respiratory pathogens in ICU was 48.5%. The results indicated 50% co-infected patient samples, more in children, of which the largest proportion were Influenza A, RSV, Streptococcus pneumoniae and Haemophilus influenzae among 2, 3, 4, 5 different combinations. Conclusion: Respiratory panel significantly improve etiological diagnosis of multiple respiratory pathogens which enhance patient care with more rational antimicrobial and/or antiviral use. Bangladesh Journal of Medical Microbiology, January 2025;19 (1):34-45